Enhancement of MSME Digitalization With Collaborative Governance: Public Values, Decision-Making, and The Administrative Context - Harsono, Subambang; Rinanda, Teja (School of Business, IPB University (SB-IPB), 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia’s economy but struggle with digitalization.Purpose: This study investigates how collaborative governance accelerates MSME digitalization through NVivo 12, focusing on the role of public values, decision-making, and administrative culture in driving digital transformation. It aims to identify key themes that strengthen governance and foster a sustainable digital ecosystem for MSMEs.Design/methodology/approach: This study examines the Fast Track Digitalization (FTD) Program in North Sumatra, a collaboration between the government, private sector, and civil society to support MSME digitalization. Data from 16–24 in-depth interviews were analyzed using thematic analysis to identify key themes in collaborative governance.Findings/Result: The study highlights the role of stakeholder collaboration and public values in accelerating MSME digitalization. It emphasizes public-private partnerships, digital literacy, and financial support, while transparent governance and flexible regulations are key to sustainable growth.Conclusion: Collaborative governance has proven effective in enhancing the competitiveness and sustainability of MSMEs in the digital era. However, research on this topic is limited, especially regarding North Sumatra, and does not fully explore the impact of emerging technologies like AI and blockchain on MSMEs' digital resilience. Future studies should investigate how these technologies can strengthen governance frameworks and contribute to long-term sustainability.Originality/value (State of the art): This research offers novelty by developing a threefold perspective that emphasizes the importance of integrating public values, collaborative decision-making, and the administrative and cultural context of policy. Keywords: MSME, digitalization, collaborative governance, threefold perspective, thematic analysis